2022
DOI: 10.2478/sjecr-2021-0068
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antidepressant Therapy on Health-Related Quality of Life in Patients with a Chronic Obstructive Pulmonary Disease and Depressive Symptoms

Abstract: Background. Symptoms of depression are often present in patients with chronic obstructive pulmonary disease (COPD) and treatment of depression may substantially improve the quality of life of such patients. The aim of our study was to investigate factors that influence the efficacy of antidepressant therapy in terms of the quality of life in patients with COPD and a depressive disorder. Materials and Methods. The study was designed as a prospective cross-sectional study and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The treatment of depression in patients with COPD requires a multidisciplinary approach [ 21 ]. However, there is a lack of research on the effects of treating depression in patients with COPD, e.g., [ 7 , 22 , 23 ], particularly in Balkan countries such as Serbia, e.g., [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of depression in patients with COPD requires a multidisciplinary approach [ 21 ]. However, there is a lack of research on the effects of treating depression in patients with COPD, e.g., [ 7 , 22 , 23 ], particularly in Balkan countries such as Serbia, e.g., [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…), and by doctors (lack of knowledge about depression in COPD, short examination period, lack of time to educate and counsel patients about depression, lack of skills to perform psychiatric assessment, etc.) [18]. Currently, there are no evidence-based recommendations for the management of COPD-related depression and the administration of antidepressants in this patient population [19].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that SSRIs may also have a beneficial effect on the symptoms of anxiety, depression, and mood disturbances experienced by patients with COPD. These medications may help improve overall well-being, reduce anxiety and depression, and enhance quality of life in COPD patients [18][19][20].…”
Section: Introductionmentioning
confidence: 99%